Samobójstwa dzieci i młodzieży przed wybuchem II wojny światowej i obecnie — co się zmieniło, co pozostało bez zmian - Ziółkowska, Anna M. (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The purpose of the article is an attempt to show the issue of suicides of children and young people in a historical perspective, by comparing the state of knowledge and methods of discussing the phenomenon from the pre-war period (until 1939) with the modern period. The first part of the work will be devoted to discussing the first papers on suicide issues that began to appear in Poland from the late nineteenth century to 1939. The second part of the article focuses on presenting the current state of knowledge on the frequency, risk factors and causes of suicide in children and young people. The last part of the work will be devoted to comparing the specifics and conditioning suicidal behavior in the discussed periods.
Keywords: samobójstwo dzieci i młodzieży; czynniki ryzyka